2003
DOI: 10.1038/sj.onc.1206146
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-associated silencing of heparan sulfate D-glucosaminyl 3-O-sulfotransferase-2 (3-OST-2) in human breast, colon, lung and pancreatic cancers

Abstract: Aberrant CpG methylations play important roles in cancer development and progression. In this study, aberrant methylations in human breast cancer were searched for using methylation-sensitive representational difference analysis (MS-RDA). A CpG island (CGI) in the 5 0 region of the heparan sulfate d-glucosaminyl 3-Osulfotransferase-2 (3-OST-2) gene was found to be hypermethylated, while its exon 2 was hypomethylated. In seven breast cancer cell lines, hypermethylation of the 5 0 region and loss of 3-OST-2 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 28 publications
1
127
1
2
Order By: Relevance
“…Primer sequences and conditions for RT-PCR product were as described previously. 17,26,31 The housekeeping gene GAPDH was used as an internal control to confirm the success of the RT reaction. Total RNA from human NME was obtained from Clontech (Palo Alto, CA).…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Primer sequences and conditions for RT-PCR product were as described previously. 17,26,31 The housekeeping gene GAPDH was used as an internal control to confirm the success of the RT reaction. Total RNA from human NME was obtained from Clontech (Palo Alto, CA).…”
Section: Cell Linesmentioning
confidence: 99%
“…13 In the present study, we determined the methylation status profile of 19 TSGs including RUNX3, 3OST2 and SOCS1 genes in nonmalignant colonic epithelia (NME), CAs and CRCs. The 19 genes were chosen for study because of their presumed or known roles in various cellular functions related to cancer development, including cell cycle regulation, tissue invasion and metastasis, JAK-STAT and TGF-b signal pathways, key components of retinoid activity, signal transduction, apoptosis, angiogenesis, putative cytokine, mitotic stress checkpoint, methyltransferase superfamily and O-sulfotransferase [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and were selected from the 6 ''hallmarks of cancer'' 32,33 (Table I). The aims of our study were as follows: (i) to clarify the methylation status of TSGs not previously studied in detail in CRC and correlate methylation with gene expression; and (ii) to investigate the role of methylation during the multistage pathogenesis of CRC, comparing the tumor profile with that of CAs and NME.…”
Section: Introductionmentioning
confidence: 99%
“…11,15,31 Our study shows that 3-OST3A was repressed and subjected to hypermethylation in all breast cancer cell lines tested except in HER2+-SKBR3 cells in which, consistently, it was expressed at relatively high level. Further analysis of the chromatin interactors at the 3-OST3A promoter showed that the epigenetic regulation not only depends upon DNA methylation, but also on repressive histone marks, and involves the recruitment of PcG proteins.…”
Section: Discussionmentioning
confidence: 63%
“…Prompted by studies from us and others pointing to an epigenetic control of 3-OST genes 11,15 , we determined whether 3-OST3A was regulated epigenetically in breast cancer cells. 3 DNA methylation analysis of the 3-OST3A promoter CpG island ( Figure S1A) showed strong hypermethylation in T-47D and MDA-derived cells, while in MCF-7 cells, hypermethylation only occurred downstream from the TSS ( Figure 1B).…”
Section: --Ost3a Is Differentially Repressed In Breast Cancer Cell Lmentioning
confidence: 99%
See 1 more Smart Citation